The clinical significance of plasma endothelin-1 in venous and portal blood of patients with portal hypertension - KURODA, Masahito; KOJIMA, Toshihiko; KAISE, Shunji; OHIRA, Hiromasa; OBARA, Katsutoshi; TAKAGI, Tohru; KASUKAWA, Reiji (Kanzo, 2000)
To investigate the significance of endothelin-1 (ET) in the pathophysiology of portal hypertension, we measured the plasma levels of ET in venous and portal blood of 37 patients with portal hypertension by means of enzyme immunoassay. The ET levels in venous blood (ETv) in patients with liver cirrhosis (LC, n=16), idiopathic portal hypertension (IPH, n=13) and primary biliary cirrhosis (PBC, n=8) were higher than those in healthy subjects. The ET levels in portal blood (ETp) in patients with IPH were significantly lower than those in patients with LC and PBC. No correlation between the levels of ETv or ETp and values of portal vein pressure (PVP) was noted in any kinds of diseases. ETp values correlated with total bilirubin values in LC patients, whereas ETv and ETp values correlated with indocyanine green dye retention rate at 15 minutes values in PBC patients. After endoscopic injection sclerotherapy (EIS) of esophagogastric varices, both ETp levels and PVP values were decreased in 4 of 6 LC patients, whereas both ETp levels and PVP values were increased in 2 of 3 PBC patients. These results suggest that ETp might play some roles in the pathophysiology of portal hypertension.